2017
DOI: 10.5604/01.3001.0009.8412
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the incidence of parotid gland tumors in the years 2005–2014

Abstract: A significant increase in the incidence of benign tumours, especially mixed and Warthin tumours, was demonstrated. There was no significant increase in the number of malignant tumours over the analysed period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 14 publications
5
19
0
4
Order By: Relevance
“…These results also revealed an increased incidence trend unlike other countries like Spain . This observation corresponds to the results reported in several other studies, including studies that reported a significant increase from 1975 to 1988 and 2005 to 2014, and other SEER‐based studies that reported an increase in incidence from 1973 to 2009 . Notwithstanding, we have found an improvement in the incidence trend of major SGC.…”
Section: Discussionsupporting
confidence: 92%
“…These results also revealed an increased incidence trend unlike other countries like Spain . This observation corresponds to the results reported in several other studies, including studies that reported a significant increase from 1975 to 1988 and 2005 to 2014, and other SEER‐based studies that reported an increase in incidence from 1973 to 2009 . Notwithstanding, we have found an improvement in the incidence trend of major SGC.…”
Section: Discussionsupporting
confidence: 92%
“…The tumors are commonly located in parotid glands followed by the submandibular glands, the minor salivary glands, and the sublingual glands. Overall, from 62% to 87% of salivary gland neoplasms are benign . The 2 most common benign neoplasms are pleomorphic adenoma and Warthin tumor, whereas the most common malignant tumor is mucoepidermoid carcinoma…”
Section: Introductionmentioning
confidence: 99%
“…Salivary gland cancers are rare, constituting 3-11% of all head and neck neoplasms and 0.2% of all malignancies, depending on the author [1][2][3]. Most occur in the sixth decade of life [4].…”
Section: Introductionmentioning
confidence: 99%